PENGARUH PRAKTEK MANAJEMEN SUMBER DAYA MANUSIA DAN IMPLEMENTASI TOTAL QUALITY MANAGEMENT TERHADAP KINERJA KARYAWAN PACKING PLANT PT. INCASI RAYA - Hanifatul Nabila (Universitas Negeri Padang, 2019)
This research aimed to analized effect of human resource management practices and the implementation of total quality management on employee performance. his research is a quantitative with a population Packing Plant PT. Incasi Raya. The analytical method used is path analysis. Path analysis results show that: 1) Human resource management practices have a positive and significant effect on the implementation of total quality management, 2) Human resource management practices have a positive and significant effect on employee performance, 3) Implementation of total quality management has a positive and significant effect on performance employee.Keywords: Practice of Human Resource Management, Implementation of Total Quality Management, Employee Performance